A Meta-Analysis of Salary Benchmarking of Engineers, BIM Modelers, and BIM Managers in the Philippines - Siman, Bennegreg P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study provides a detailed meta-analysis of salaries for engineers, BIM modelers, and BIM managers in the Philippines, emphasizing how geographical location, experience level, industry sector, qualifications, and market trends influence compensation. The analysis incorporates data from a variety of sources, including academic publications, industry reports, and government statistics, to provide a detailed understanding of salary variations within different professions. Findings show significant salary differences based on their geographical location. Professionals in Metro Manila have considerably larger wages than those in provincial re-gions. Experience level is also important when it comes to salary increas-es which can be observed when professionals advance from entry-level to senior roles. Salary levels are also influenced by the industry, with tech-nology, building, and infrastructure development sectors offering highest compensation. Additional qualifications and certificates enhance salary opportunities, reflecting the value of particular skills and expertise. The purpose of this study is to write a meta-analysis of salary benchmarks for BIM modelers, engineers, and BIM managers in the Philippines emphasiz-ing how factors such as geographical location, experience level, industry sector, qualifications, and market trends influence compensation. The analysis includes seven studies that were published between 2019 and 2024 to capture recent salary patterns in these professions. The study shows the importance of understanding these important variables in de-veloping successful compensation methods, optimizing talent acquisition, and promoting retention in the engineering and construction sectors in the Philippines. The insights provided are expected to allow stakeholders to make informed decisions to build a competitive and thriving workforce in these critical industries.